Hepatocellular carcinoma in thalassaemia: an update of the Italian Registry. (3rd July 2014) - Borgna‐Pignatti, Caterina; Garani, Maria Chiara; Forni, Gian Luca; Cappellini, Maria Domenica; Cassinerio, Elena; Fidone, Carmelo; Spadola, Vincenzo; Maggio, Aurelio; Restivo Pantalone, Gaetano; Piga, Antonio; Longo, Filomena; Gamberini, Maria Rita; et al.
Summary The risk of developing hepatocellular carcinoma (HCC) in patients with thalassaemia is increased by transfusion‐transmitted infections and haemosiderosis. All Italian Thalassaemia Centres use an ad hoc form to report all diagnoses of HCC to the Italian Registry. Since our last report, in 2002, up to December 2012, 62 new cases were identified, 52% of whom were affected by thalassaemia major (TM) and 45% by thalassaemia intermedia (TI). Two had sickle‐thalassaemia (ST). The incidence of the tumour is increasing, possibly because of the longer survival of patients and consequent longer exposure to the noxious effects of the hepatotropic viruses and iron. Three patients were hepatitis B surface antigen‐positive, 36 patients showed evidence of past infection with hepatitis B virus (HBV). Fifty‐four patients had antibodies against hepatitis C virus (HCV), 43 of whom were HCV RNA positive. Only 4 had no evidence of exposure either to HCV or HBV. The mean liver iron concentration was 8 mg/g dry weight. Therapy included chemoembolization, thermoablation with radiofrequency and surgical excision. Three patients underwent liver transplant, 21 received palliative therapy. As of December 2012, 41 patients had died. The average survival time from HCC detection to death was 11·5 months (1·4–107·2 months). Ultrasonography is recommended every 6 months to enable early diagnosis of HCC, which is crucial to decrease mortality.